ANALISIS KELAYAKAN FINANSIAL BUDIDAYA JAMUR TIRAM PUTIH DI SAMARINDA - Robin ,Titin, PATKU ROHMAN (EKONOMIA, 2015)
This study aimed to analyze the costs, revenues cultivation of oyster mushroom, acceptance of the cost (R/C ratio), return on costs (B C ratio), the calculation of relevant costs, Break Event Point (BEP) and capital budgeting (Payback Period , Return On Investmen, Net Present Value) to look at the feasibility of oyster mushroom cultivation in Samarinda.Based on the survey results revealed huge investment costs incurred by using LPG fuel is greater than the cost of the investment using wood fuel in the sterilization process with the difference in cost of USD 1,550,000, operating costs using LPG fuel is greater than the operating costs with fuel timber with a difference of USD 825 833, income using wood fuel is more profitable compared to revenues with LPG fuel with a difference of USD 51 666, the profit in one period using wood fuel is more profitable compared with a profit with LPG fuel with a difference of USD 877 499, R/C ratio and B/C ratio of white oyster mushroom business in Samarinda can already be said to be feasible because of the value of R/C ratio> 1 and the B/C ratio> 0 and BEP stating the business is profitable and beneficial